2022
DOI: 10.1002/ejoc.202201172
|View full text |Cite
|
Sign up to set email alerts
|

The Journey to Fluorescent Bullvalenes: Pitfalls and Prospects

Abstract: Dedicated to Professor Waldemar Adam on the occasion of his 85th birthdayA dinaphthoylmethyl-substituted bullvalene derivative is presented that exhibits excimer fluorescence. It is demonstrated that the fluxional bullvalene core supports the excimer formation of the aroyl substituents, thus offering the opportunity to monitor externally induced structural changes by fluorescence spectroscopy, as exemplarily shown by fluorimetric analysis of host-guest interactions of the diaroylbullvalene with metal cations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…As such an assembly consists of only one bullvalene unit, it has a smaller number of possible isomers and, therefore, a significantly reduced complexity, which in turn should facilitate its analysis. Coincidentally, during our studies on aryl‐substituted bullvalene derivatives, [16] we made accessible a bullvalene‐harmane conjugate 1 that appeared to have the main prerequisites to act as such a chelating ligand (Figure 2). Specifically, the harmane, a ß‐carboline, contains a lateral pyridine unit [17] that is known to complex several transition metal ions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As such an assembly consists of only one bullvalene unit, it has a smaller number of possible isomers and, therefore, a significantly reduced complexity, which in turn should facilitate its analysis. Coincidentally, during our studies on aryl‐substituted bullvalene derivatives, [16] we made accessible a bullvalene‐harmane conjugate 1 that appeared to have the main prerequisites to act as such a chelating ligand (Figure 2). Specifically, the harmane, a ß‐carboline, contains a lateral pyridine unit [17] that is known to complex several transition metal ions.…”
Section: Figurementioning
confidence: 99%
“…SI, Figure S38). Additional 1D-selec-tive TOCSY experiments showed that the isomeric population is dominated by the two most frequently observed isomers [3,6,8,11,16,18] 1 a (60 %) and 1 b (40 %) in CDCl 3 solution at À 50 °C (Figure 2; cf. SI, Figure S40).…”
mentioning
confidence: 99%